ANALISIS PUTARAN PULI RODA GIGI FLYWHEEL PENGGERAK BEBAN PUTARAN RODA GIGI TRANSMISI OTOMOTIF - Marpaung, Parlindungan Pandapotan (Pusat Riset dan Inovasi Nasional, 2022)
The electric power of an ac electric motor of Pin = 310.4 watts produces rotation of the output shaft which is used to drive the flywheel gear pulley to produce a rotational speed of Vrpm(in) = 347.8 rpm with a torque parameter of Tin = 8.53 Nm which is transmitted to each each load rotation of the gear pulley of the forward transmission-1 to the forward transmission-4 and the reverse transmission. The results of the research on the speed of the flywheel gear pulley, the Vrpm(in) parameter of 347.8 rpm, was transmitted to the forward-1 transmission gear load resulting in Vrpm(forward-1) = 89.6 rpm, torque Tout(forward-1) = 33.1 Nm and mechanical power Pout(forward-1) = 191.87 watts. Then it is transmitted to the forward-2 transmission gear load producing Vrpm (forward-2) = 162.7 rpm, Tout (forward-2) = 17.34 Nm and Pout (forward-2) = 100.51 watts. Then transmitted to the gear load of the forward-3 transmission is Vrpm(forward-3) = 248.2 rpm, Tout(forward-3) = 11.36 Nm and Pout(forward-3) = 65.85 watts. Transmitted to the transmission gear load forward-4 produces Vrpm (forward-4) = 347.8 rpm, Tout (forward-4) = 8.11 N and Pout (forward-4) = 47.01 watts. To go to the reverse transmission gear load produces Vrpm (reverse) = 75.4 rpm, Tout (backward) = 37.44 Nm and Pout (reverse) = 217.03watt.